Chronic Rhinosinusitis Patient with Nasal Polyp Characteristics at Otorhinolaryngology-Head and Neck Surgery Outpatient Clinic, Dr. Hasan Sadikin General Hospital, Bandung - Dina Riana; Arif Dermawan; Wijana Wijana; Ongka Muhammad Saifuddin (Faculty of Medicine Universitas Padjadjaran, 2016)
Objective: To evaluate chronic rhinosinusitis (CRS) with nasal polyp (NP) characteristics in patients with routine visits to the Otolaryngology-Head and Neck Surgery outpatient clinic of Dr. Hasan Sadikin General Hospital, Bandung.Methods: This descriptive retrospective cross-sectional study was conducted at the Rhinology-Allergy Outpatient Clinic, Departement of Otolaryngology-Head and Neck Surgery, Dr. Hasan Sadikin General Hospital, Bandung, in the period of January 2014 to December 2014. Data were obtained from medical records and the sampling method used was total sampling. A total of 100 CRS with NP patients were evaluated. Nasal endoscopy examinations were performed. Patients were classified based on age into 10–20 years, 21–31 years, 32–42 years, 43–53 years, and >54 years groups. Results: Chronic rhinosinusitis with NP incidences were mostly found in male patients compared to females. There were several CRS cases with NP risk factors, including smoking and allergy. Conclusions: In the study, CRS with NP patients may possibly have one or more risk factors. Smoking is the major risk factor from CRS with NP after allergy. Keywords: Nasal polyp, nasal endoscopy, rhinosinusitis, risk factor DOI: 10.15850/ijihs.v4n2.834